Stability Analysis and Protection Measures of Large Section Tunnel in Coal Rich Weak Rock Stratum. (30th August 2021) - Zhou, Guannan; Zhao, Zijiang; Song, Zhanping; Wang, Hongjian
Abstract : Due to poor engineering geological conditions of Liujiazhuang tunnel on Shanghai-Kunming Passenger Dedicated Line, the large deformation of weak rock occurs repeatedly during tunnel construction. In this paper, the large-scale finite element software ABAQUS is used to simulate the construction process of a large-section tunnel in weak surrounding rock. It is found that when tunnel face passes through the coal seam, the displacement and stress simulated by the bench method increase abruptly. The maximum stress reaches up to 18 MPa, and displacement reaches 45 mm, which is about twice when without crossing coal seam. It is technically feasible to use the bench method for tunnel construction, under the condition when large settlements is allowed; additionally, the bench method has better technical and economic benefits than that of the CD method. Through the comparative analysis of onsite monitoring data and numerical simulation results, it can be seen that the tunnel is in a dangerous state when passing through the coal seam and measures such as strengthening support or auxiliary advance support should be taken immediately to control the surrounding rock and to ensure tunnel construction safety.